Zero blood alcohol concentration limits for drivers under 21: lessons from Canada. Issue 2 (3rd April 2008) - Chamberlain, E; Solomon, R
Abstract : Graduated licensing programs (GLPs) that include zero or low blood alcohol concentration (BAC) restrictions have proven to be a popular and effective measure for improving traffic safety among young people. However, a major drawback of such programs, at least in Canada, is that the BAC restriction is lifted on completion of the GLP, which typically occurs around the age of 18 or 19. This corresponds to the legal drinking age in Canada, a time when alcohol consumption and rates of binge drinking increase. It is not surprising, then, that 18–20 year-old drivers are dramatically overrepresented in alcohol-related deaths and injuries. One way to address this problem is to raise the legal drinking age, as has occurred in the United States. In jurisdictions, like Canada, that are unlikely to raise the legal drinking age, other measures are necessary to separate drinking from driving among 18–20 year-olds. This article recommends that the zero BAC restrictions be extended beyond the completion of the GLP, until drivers reach the age of 21. The scientific evidence for such a measure is reviewed, and the growing government support for enacting such BAC limits in Canada is described.